The tendencies of climate change and water regime of the middle- lower part in the basin of Southern Bug River (in the region of location of the South-Ukrainian Nuclear Power Plant) - Zabulonov, Yu.L.; Boychenko, S.G.; Zholudenko, O.O.; Buhera, M.A. (Геофизический журнал, 2018)
Feature of climate change and runoff for the middle-lower part of the basin of the Southern Bug River (in location of the South-Ukrainian Nuclear Power Plant) of the second half of the XX century and at the beginning of the XXI century are analyzed. Проанализированы особенности изменения климата и водности для средне-нижней части бассейна р. Южный Буг (в регионе расположения Южно-Украинской атомной электростанции (ЮУАЭС)) во второй половине XX в. - в начале XXI в. Проаналізовано особливості зміни клімату та водності для середньо-нижньої частини басейну р. Південний Буг (у регіоні розташування Южно-Української атомної електростанції (ЮУ АЕС)) в другій половини XX ст. — на початку XXI ст.